Exploration of Anthelmintic, Blood Coagulant, Diuretic and Laxative Activities of Different Solvent Fractions of Flagellaria Indica Leaves - Karmakar, Utpal Kumar; Paul, Animesh; Kundu, Pritam; Paul, Progga Paramita (Jordan Journal of Pharmaceutical Sciences, 2023)
Flagellaria indica (Family: Flagellariaceae) is a common climbing plant found primarily in tropical regions of many countries. The plant has various traditional uses, although most of them lack scientific published reports. The crude ethanolic extract of F. indica leaves was fractionated based on polarity using water, ethyl acetate, and n-hexane. Biological screening was conducted on the anthelmintic, blood coagulation, diuretic, and laxative activities of the water, ethyl acetate, and n-hexane fractions of F. indica leaves. In the anthelmintic test, the n-hexane fraction showed a moderate effect with paralysis times of 16.79 and 13.62 minutes and death times of 27.34 and 21.81 minutes, respectively, at doses of 25 and 50 mg/mL.In the blood coagulant test, only the water fraction showed a notable effect. The clotting times were 4.33, 6.02, 7.68, and 8.32 minutes, respectively, at doses of 200, 100, 50, and 25 mg/mL. Diuretic activity was performed to determine the increase in the volume of excreted urine, and electrolyte analysis of urine was performed to determine pH, density, conductance, and Na+, Cl-, K+ levels, as well as natriuretic, kaliuretic, saluretic, and CAI indexes. The ethyl acetate fraction showed better diuretic activity than the n-hexane fraction, while the water fraction did not reveal a notable diuretic effect. The Na+, Cl-, K+, natriuretic, and saluretic indexes were found satisfactory in the ethyl acetate fraction, and the CAI index was better in the n-hexane fraction. In the laxative test, the n-hexane fraction showed the best laxative properties, with an increase in stool weight of 38% and 54% at doses of 250 and 500 mg/kg, respectively. These results suggest that different fractions of F. indica leaves contain distinct phytochemicals that may be responsible for these biological effects. The isolation of bioactive compounds could help justify its traditional uses in modern medicine.